Thoracic degenerative disc pathologies in geriatric patients - Akgün, Ayşe Serap; Yavaş Dinç, Arzu (Güneş Kitabevi Ltd. Şti, 2020)
Introduction: This study investigates the incidence and localization of thoracic degenerative disc pathologies, such as bulging and herniation, in geriatric patients.Materials and Methods: Between January 2015 and August 2019, a total of 171 patients were retrospectively examined in the study. The patients were admitted for dorsalgia and underwent magnetic resonance imaging (MRI) of the thoracic vertebra. All patients were examined for disc and endplate degeneration, bulging and/or disc herniation, and Schmorl nodes.Results: Disc bulging/herniation was diagnosed in 534 (26%) of the overall total of 2052 intervertebral disc levels; 206 (10%) of these had bulging but no herniation. The location most commonly affected by bulging was T10-11 (n=46, 2.25%), followed by T11-T12 (n=45, 2.1%) Disc herniation was present in 329 (15.9%) of the levels; herniation was most common at T11-12 (n=51, 15.5%).Conclusion: The intervention of music therapy was found to have an effect in reducing anxiety and increasing sleep quality of patients. Music therapy can be used as an alternative method of treating the anxiety and increasing the sleep quality of geriatric hematology patients.
Keywords: Geriatric Assessment; Back Pain; Thoracic Vertebrae; Magnetic Resonance Imaging